2015
DOI: 10.3389/fpsyg.2015.01795
|View full text |Cite
|
Sign up to set email alerts
|

Social Identities as Pathways into and out of Addiction

Abstract: There exists a predominant identity loss and “redemption” narrative in the addiction literature describing how individuals move from a “substance user” identity to a “recovery” identity. However, other identity related pathways influencing onset, treatment seeking and recovery may exist, and the process through which social identities unrelated to substance use change over time is not well understood. This study was designed to provide a richer understanding of such social identities processes. Semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
178
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(191 citation statements)
references
References 58 publications
(79 reference statements)
9
178
1
3
Order By: Relevance
“…Indeed, in line with the Social Identity Model of Cessation Maintenance (Frings & Albery, 2015), and the more recent Social Identity Model of Recovery (Best et al, 2016), work with those suffering from substance use problems has shown that the introduction, development, and maintenance of 'recovery' or 'non-substance using' identities can enhance treatment outcomes amongst those with substance use disorder (e.g. Beckwith, Best, Dingle, Perryman, & Lubman, 2015;Dingle et al, 2015;Dingle, Stark, Cruwys, & Best, 2014).…”
Section: Group Identification and Health Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in line with the Social Identity Model of Cessation Maintenance (Frings & Albery, 2015), and the more recent Social Identity Model of Recovery (Best et al, 2016), work with those suffering from substance use problems has shown that the introduction, development, and maintenance of 'recovery' or 'non-substance using' identities can enhance treatment outcomes amongst those with substance use disorder (e.g. Beckwith, Best, Dingle, Perryman, & Lubman, 2015;Dingle et al, 2015;Dingle, Stark, Cruwys, & Best, 2014).…”
Section: Group Identification and Health Behaviourmentioning
confidence: 99%
“…Cruwys, Haslam, Fox, & McMahon, 2015;Dingle, Cruwys, & Frings, 2015). This is because defining oneself in terms of a specific identity (such as a substance using identity) may encourage behaviour in accordance with this identity (e.g.…”
Section: Group Identification and Health Behaviourmentioning
confidence: 99%
“…Furthermore, addiction is conceived as a disease and addicted person as its victim. Current research shows that the truth is probably elsewhere: addiction often arises as part of complex processes that primarily involve close relationships (Dingle 2015). Branch (2011) argues that addiction is also largely influenced by the decision and will of the user.…”
Section: Release Of Legislationmentioning
confidence: 99%
“…In addition to rapid change of social structure, efforts to adapt to new life styles, unemployment, poverty, access to drugs, and culture pave the way for addiction. Dingle, Cruwys and Frings (2015) draw attention the literature based on individual factors about addiction and emphasize the importance of social factors, which are involved in every stage of the development of and recovery from addiction.…”
Section: Drug Addiction In Childrenmentioning
confidence: 99%